2016
DOI: 10.1111/cpr.12290
|View full text |Cite
|
Sign up to set email alerts
|

p75 neurotrophin receptor regulates differential mineralization of rat ectomesenchymal stem cells

Abstract: p75NTR participated in tooth germ development stages and mediated differential mineralization of EMSCs. p75NTR played a critical role in regulating the potential of differential mineralization of EMSCs. Mage-D1 seemed to act as a bridge in the underlying mechanism of effects of p75NTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 69 publications
3
32
0
Order By: Relevance
“…It has been used to successfully select cranial neural crest‐derived EMSCs (p75 + EMSCs) in vitro, providing a useful stem cell model for research on tooth morphogenesis . Moreover, p75NTR has been reported to participate in tooth morphogenesis and dental hard tissue mineralization . However, most molecular signatures on the effect of p75NTR in tooth morphogenesis remain to be uncovered, and the elusive mechanism underlying tooth development has severely restricted dental tissue engineering thus far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used to successfully select cranial neural crest‐derived EMSCs (p75 + EMSCs) in vitro, providing a useful stem cell model for research on tooth morphogenesis . Moreover, p75NTR has been reported to participate in tooth morphogenesis and dental hard tissue mineralization . However, most molecular signatures on the effect of p75NTR in tooth morphogenesis remain to be uncovered, and the elusive mechanism underlying tooth development has severely restricted dental tissue engineering thus far.…”
Section: Discussionmentioning
confidence: 99%
“…This is because this stem cell population gives rise to cells of the dental papilla and dental follicle, which subsequently form all tooth tissues except for enamel. In subsequent studies, p75NTR was reportedly positively related to the in vitro mineralization of EMSCs and promoted EMSCs differentiating into cells such as cementoblasts and odontoblasts . We previously revealed that p75NTR was strongly expressed at the cap and bell stages during tooth development and showed similar expression patterns as those of the mineralization‐related marker Runx2, implying the important role of p75NTR in tooth morphogenesis, especially during dental hard tissue mineralization.…”
Section: Introductionmentioning
confidence: 90%
“…p75NTR heterozygous pregnant mice at E12.5d were obtained, and the embryonic maxillofacial processes were dissected from each embryo separately, while the remaining tissue was used for genotyping as previously reported 31. Then, primary EMSCs were extracted according to our previous study 23. Briefly, we used 1% trypsin/1 mmol/L EDTA solution (Sigma, USA) to digest the minced tissue at 37°C for 10 minutes and then stopped digestion with DMEM/F12 (Gibco, USA) containing 10% FBS (Gibco, USA).…”
Section: Methodsmentioning
confidence: 99%
“…But the enhanced expression of p75NTR did not result in the increase in cell proliferation, indicating that p75NTR was not involved in the regulation of the proliferation in EMSCs harvested in the present study. In our previous study, TrkA was expressed neither in the embryonic phases of EMSCs nor during the mineralized induction. Luukko et al also reported that TrkA mRNAs failed to be detected by in situ hybridization in rat first molars at any developmental stage except the trigeminal ganglia.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, evidence showed that p75NTR is not only used to select the cells originating from CNC, but also to participate in the regulation of tooth morphogenesis . In our previous studies, both histological and molecular biological evidence suggested that p75NTR plays an important role in the initiation of tooth morphogenesis . However, its definite effects and molecular mechanism are not clear yet.…”
Section: Introductionmentioning
confidence: 90%